2008
DOI: 10.1128/jvi.01162-08
|View full text |Cite
|
Sign up to set email alerts
|

Block to the Production of Full-Length B19 Virus Transcripts by Internal Polyadenylation Is Overcome by Replication of the Viral Genome

Abstract: The pre-mRNA processing strategy of the B19 virus is unique among parvoviruses. B19 virus-generated pre-mRNAs are transcribed from a single promoter and are extensively processed by alternative splicing and alternative polyadenylation to generate 12 transcripts. Blockage of the production of full-length B19 virus transcripts at the internal polyadenylation site [(pA)p] was previously reported to be a limiting step in B19 virus permissiveness. We show here that in the absence of genome replication, internal pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
113
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(117 citation statements)
references
References 49 publications
4
113
0
Order By: Relevance
“…We and others (11,12,14,16,17) have analyzed the transcription profile obtained when COS-7 cells were transfected with a replication-competent, nearly full-length B19V genome and found that it resembles that observed during B19V infec- …”
Section: Human Parvovirus B19 (B19v)mentioning
confidence: 94%
See 4 more Smart Citations
“…We and others (11,12,14,16,17) have analyzed the transcription profile obtained when COS-7 cells were transfected with a replication-competent, nearly full-length B19V genome and found that it resembles that observed during B19V infec- …”
Section: Human Parvovirus B19 (B19v)mentioning
confidence: 94%
“…We and others (11,12,14,16,17) have analyzed the transcription profile obtained when COS-7 cells were transfected with a replication-competent, nearly full-length B19V genome and found that it resembles that observed during B19V infec-tion of B19V-permissive cells. Using this system, we have identified multiple cis-acting elements that facilitate inclusion of the second exon (from the A1-1/A1-2 acceptor site to the D2 donor site), which was confirmed by monitoring transcription profiles during B19V infection of human primary erythroid progenitor cells (18).…”
Section: Human Parvovirus B19 (B19v)mentioning
confidence: 95%
See 3 more Smart Citations